Unobserved human capital and firm-sized premium - Hannu Piekkola (The Research Institute of the Finnish Economy (ETLA), 2000)
This paper examines wage compensations and worker mobility in firms with different size using linked employer-employee Finnish data over the period 1989-1996. We show that the unobserved human capital component of wages is increasing in firm size and explains a substantial share of the higher wages in large firms. We suggest alternative explanations for this. To begin with, high wages lead directly to larger firm size through lower job search of employers. In addition, large firms can build reputation wages as they have a longer employment history. Both explanations are consistent in our finding that the payments on unobserved human capital lower excess worker reallocation. High-wage earners in large firms can also be risky workers with an option value on good performance. In contrast to previous explanations, this increases job and worker turnover. We also claim that large firms substitute high wages for large monitoring costs. Small firms have more information on the worker effort of their employees and can monitor employees better than large firms. – wages ; compensation policy ; productivity ; industry differentials – – Tutkimus tarkastelee palkanmuodostusta ja työvoiman liikkuvuutta erikokoisissa yrityksissä Suomessa yhdistetyssä yritys-työntekijä aineistossa ajanjaksolla 1989-1996. Ei-havaittava inhimillinen pääoma kasvaa yrityskoon mukaan ja on merkittävin selittäjä suurten yritysten korkeammille palkoille. Suurilla yrityksillä on parempi tunnettuvuus ja maine. Tämä ja korkeat palkat sinänsä vähentävät työntekijöiden hakeutumista muualle töihin. Suurissa yrityksissä henkilöstön valvonta on vaikeampaa, mitä kompensoidaan korkeammilla palkoilla. Samalla suuret yritykset maksavat vähemmän kannustimiin tai voitonjakoon perustuvia palkkoja. Korkeat palkat ovat paremmin seurausta siitä, että yritykset rekrytoivat uusia työntekijöitä korkealla palkalla ja huonosti menestyvät työntekijät irtisanotaan tai he hakeutuvat muualle töihin.
Keywords: J21; J31; J50; C22; 330; Lohntheorie; Humankapital; Lohnbildung; Finnland